A short note on sign changes and non-vanishing of Fourier coefficients of half-integral weight cusp forms - Kohnen, Winfried (Abhandlungen aus dem Mathematischen Seminar der Universität Hamburg, 2022)
We study sign changes and non-vanishing of a certain double sequence of Fourier coefficients of cusp forms of half-integral weight.
Online veröffentlicht: 14. Dezember 2022
Gesehen am 04.04.2023